Gestión del Talento Humano y Turismo Comunitario en la comunidad La Moya, del cantón Riobamba. - Samaniego Tingo, Adrian Ramiro (2023)
This research is developed with the main objective of analyzing the relationship between the management of human talent and community tourism in the La Moya community, in the Riobamba canton, since it has not been consolidated as an important tourist activity and the lack of knowledge in community about tourism. It is a relatively new action in the tourism field. The methods used in the development of the research are descriptive, field documentary with a correlational design of both the independent variable (Human Talent Management) and the dependent variable (Community Tourism). It is non-experimental because the. The research study was not altered or manipulated. Likewise, with the purpose of obtaining the results of the research, the same survey technique was used which was applied to the members who work at the La Moya community tourism center and to professionals involved and with knowledge in community tourism. In relation to the results obtained, it is considered that it is essential to create a manual of human talent management processes in order to contribute to the fulfillment of the proposed goals and highlight the importance of human talent in the different areas and improve efficiency. and effectiveness of each of the collaborators.